2008
DOI: 10.1186/1475-925x-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of MRI induced heating on metallic leads: Experimental measurements of 374 configurations

Abstract: Background: MRI induced heating on PM leads is a very complex issue. The widely varying results described in literature suggest that there are many factors that influence the degree of heating and that not always are adequately addressed by existing testing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 154 publications
(147 citation statements)
references
References 16 publications
5
141
0
1
Order By: Relevance
“…The system is installed at the Department of Technology and Health of the Italian National Institute of Health and has been specially designed to provide a controlled exposure for MRI safety testing with regards to the RF field. Systems with the same features have been widely used in previous published studies (17,(22)(23)(24). It has also been demonstrated that, given the same implant configuration and the same WB-SAR delivered to the phantom, the induced heating inside the isolated birdcage coil is comparable with the one obtained in an actual MRI system using clinical MRI sequences (23).…”
Section: Exposure Systemmentioning
confidence: 87%
See 4 more Smart Citations
“…The system is installed at the Department of Technology and Health of the Italian National Institute of Health and has been specially designed to provide a controlled exposure for MRI safety testing with regards to the RF field. Systems with the same features have been widely used in previous published studies (17,(22)(23)(24). It has also been demonstrated that, given the same implant configuration and the same WB-SAR delivered to the phantom, the induced heating inside the isolated birdcage coil is comparable with the one obtained in an actual MRI system using clinical MRI sequences (23).…”
Section: Exposure Systemmentioning
confidence: 87%
“…The simulator consists of a torso-shaped transparent PVC phantom of the size of a 70 kg male and of an internal volume of about 30 L. The leads were fixed on a PVC grid placed inside the phantom. The use of human-shaped phantoms, even if not prescribed by technical standards, has been already used to complement measurements obtained with standardized phantoms (17,23). It has been demonstrated that the geometry of the phantom can affect the amount of the induced heating at the implant tip (17).…”
Section: Phantomsmentioning
confidence: 99%
See 3 more Smart Citations